Phase transformation in CaCO3 polymorphs: a spectroscopic, microscopic and diffraction study - Schmidt, Moritz; Stumpf, Thorsten; Walther, Clemens; Geckeis, Horst; Fanghänel, Thomas (Journal of colloid and interface science, 2010)
This study presents results of the phase transformation from Cm(III) and Eu(III) doped vaterite to calcite. This transformation of one solid solution (An/Ln:vaterite) to another (An/Ln:calcite) was observed by powder X-ray diffraction and scanning electron microscopy.
Gesehen am 13.06.2023